Evaluación de la calidad de servicio, en las cooperativas de ahorro y crédito, del segmento 4, de la ciudad de Ambato, provincia de Tungurahua - Suasnavas Condor, Dayanna Maricela (2019)
Currently due to the increased competitiveness of financial institutions is relevant to know what are the factors that contribute to the service quality that is provided by each of the organizations, implementing different strategies. Besides, it is important to investigate the differences between the institutions and establish appropriate techniques in the quality process in order to ensure their solidity. The goal research is to evaluate the service quality which is perceived by the members, into Savings and Credit Cooperatives, four segment in Ambato City, Tungurahua Province. The methodology applied is quantitative to collect data and interpret it through analysis within the context in which it is developed. An intentional sample of 244 partners was taken applying a non-experimental design into natural environment. Servqual Model survey was applied as a data collection technique. This tool is used to exclusively evaluate the service quality. Also, it consists of 20 questions that contain five dimensions, taking into account the following factors: tangibility, reliability, sensitivity, security and empathy, which are integrated into the applied tool. The results showed dissatisfaction with respect to the security dimension, it was evidenced that there is a positive comparison between the service quality and customer satisfaction. In this way, the lack of mastery, knowledge and skills by employees of Credit unions. Once the main findings are known, training programs on the service quality are proposed. It is leaded to Savings and Credit Cooperatives’ staff, in order to create competitive advantages for financial institutions.Keywords: quality, service, client, financial institutions, Servqual Model